Role of calcium in the response of cellular metabolism to epibrassinolide in transgenic tobacco cax1 plants - Kretynin, S. V.; Bondarenko, O. M.; Kravets, V. S.; Khripach, V. A.; Kukhar, V.P. (Reports of the National Academy of Sciences of Ukraine, 2015)
The role of calcium was investigated in the response of cellular metabolism to 24-epibrassinolide (EBL) in transgenic plants of Nicotiana tabacum ecotype KY-160 and tobacco cax1 transgenic plants created from them that express a coding part of H+/Ca2+ vacuolar antiporter CAX1 of Arabidopsis. It was established that the EBL activates the antioxidant system (superoxide dismutase, ascorbate peroxidase, and glutathione reductase) and increases the levels of superoxide anion radical and reduced glutathione. It was shown that a disturbance of intracellular calcium homeostasis reduces plant responses to exogenous EBL. Reduction of the enzymatic activity of the ascorbateglutathione cycle — ascorbate peroxidase and glutathione reductase — was observed in response to glucose-6-phosphate dehydrogenase inhibitor.